An Empirical Study of Sectoral-Level Capital Investments in New Zealand - Weshah Razzak (New Zealand Government, The Treasury, 2014)
I extend the Glick and Rogoff (1995) aggregate time-series, empirical, intertemporal model of country-investment (and the current account) to a sectoral-level, and estimate it for New Zealand. I fit the model to panel data of eleven industries from 1988-2009. The sectoral-level investment growth is a function of lagged investment level, sector-specific TFP shocks, country-specific TFP shocks, and global TFP shocks. The estimates seem robust to government spending shocks and Terms of Trade shocks.
Keywords: E2; C2; C3; 330; Investments; sectoral-level; TFP shocks; panel data; Investition; Branche; Produktivitätsentwicklung; Schock; Branchenentwicklung; Panel; Neuseeland